Analysis of copy number variations and possible candidate genes in spontaneous abortion by copy number variation sequencing - Bai, Wei; Zhang, Qi; Lin, Zhi; Ye, Jin; Shen, Xiaoqi; Zhou, Linshuang; Cai, Wenpin (Frontiers in Endocrinology, 2023)
In this study, copy number variation sequencing (CNV-seq), a Next-Generation Sequencing (NGS) technology, was utilized to investigate the potential correlation between chromosomal abnormalities and spontaneous abortion. We analyzed Copy Number Variations (CNVs) in 395 aborted fetal specimens from spontaneous abortion patients. The results showed that out of the 395 cases, 67.09% of the fetuses had chromosomal abnormalities, including numerical abnormalities, structural abnormalities, and mosaicisms. We collected correlated data, including maternal age, gestational week, and Body Mass Index (BMI), and analyzed their relationship with the CNVs. Maternal age is an important risk factor for fetal chromosomal abnormalities, and the proportion of autosomal trisomy in abnormal karyotypes increases with maternal age, while polyploidy decreases. Furthermore, the proportion of abnormal karyotypes with mosaic decreases as gestational age increases, while the frequency of polyploidy and sex chromosome monosomy increases. Gene enrichment analysis identified potential miscarriage candidate genes and functions, as well as pathogenic genes and pathways associated with unexplained miscarriage among women aged below or over 35 years old. Based on our study, it can be inferred that there is an association between BMI values and the risk of recurrent miscarriage caused by chromosomal abnormalities. Overall, these findings provide important insights into the understanding of spontaneous abortion and have implications for the development of personalized interventions for patients with abnormal karyotypes.